How Scary Is the Risk of Automation? Evidence from a Large Scale Survey Experiment - Maria Alejandra Cattaneo; Christian Gschwendt; Stefan C. Wolter (Institute of Labor Economics (IZA), 2024)
Advances in technology have always reshaped labor markets. Automating human labor has lead to job losses and creation but most of all, for an increasing demand for highly skilled workers. However, emerging AI innovations like ChatGPT may reduce labor demand in high skilled occupations previously considered "safe" from automation. While initial studies suggest that individuals adjust their educational and career choices to mitigate automation risk, it is unknown what people would be willing to pay for a reduced automation risk. This study quantifies this value by assessing individuals' preferences for occupations in a discrete-choice experiment with almost 6'000 participants. The results show that survey respondents are willing to accept a salary reduction equivalent to almost 20 percent of the median annual gross wage to work in an occupation with a 10 percentage point lower risk of automation. Although the preferences are quite homogeneous, there are still some significant differences in willingness to pay between groups, with men, younger people, those with higher levels of education, and those with a higher risk tolerance showing a lower willingness to pay for lower automation risk.
Keywords: J24; O33; 330; artificial intelligence; automation; willingness to pay; survey experiment